A particle method for two‐phase flows with compressible air pocket. (1st April 2016) - Luo, M.; Koh, C. G.; Bai, W.; Gao, M.
Summary: When using particle methods to simulate water–air flows with compressible air pockets, a major challenge is to deal with the large differences in physical properties (e.g., density and viscosity) between water and air. In addition, the accurate modeling of air compressibility is essential. To this end, a new two‐phase strategy is proposed to simulate incompressible and compressible fluids simultaneously without iterations between the solvers for incompressible and compressible flows. Water is modeled by the recently developed 2‐phase Consistent Particle Method for incompressible flows. For air modeling, a new compressible solver is proposed based on the ideal gas law and thermodynamics. The formulation avoids the problem of determining the actual sound speed that is dependent on the temperature and is therefore not necessarily constant. In addition, the compressible air solver is seamlessly integrated with the incompressible solver 2‐phase Consistent Particle Method because they both use the same predictor–corrector scheme to solve the governing equations. The performance of the proposed method is demonstrated by three benchmark problems as well as an experimental study of sloshing impact with entrapped air pockets in an oscillating tank. Copyright © 2016 John Wiley & Sons, Ltd.